Praktikum Pembuatan Pupuk Bokasi untuk Pemanfaatan Tanaman Hortikultura (Limbah Jadi Pupuk) di Kelurahan Ngedukelu - Prisko Yanuarius Djawaria Pare; Maria Sindrela Wea; Apolonia Bela; Gaudensia Nio Nuwa; Stefania Bibiana Bue; Maria Magdalena Kae; Maria Orliana Adin; Hendrika Suri; Maria Margaretha Tawa; Maria Yosefa PignaTelin Riu (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2026)
Bokashi fertilizer is an organic fertilizer produced through the fermentation of organic materials with the assistance of Effective Microorganisms (EM-4), which functions to improve soil fertility and crop productivity. This activity aimed to provide education and practical skills to the community of Ngedukelu Village in utilizing local organic waste as bokashi fertilizer, so that it can serve as an alternative to inorganic fertilizers in horticultural crop cultivation. The method applied was a participatory approach through a series of extension activities, training sessions, hands-on practice, and field assistance. The raw materials for bokashi fertilizer were sourced from easily available local organic waste, such as livestock manure, rice husks, straw, and household vegetable waste. The results showed that the produced bokashi fertilizer had good maturity characteristics, indicated by a dark brown to blackish color, a crumbly texture, a distinctive fermented odor, and the appearance of white filaments as indicators of microbial activity. Application of bokashi fertilizer to horticultural crops such as chili, mustard greens, and legumes demonstrated improved plant growth, greener leaves, and greater resistance to pest attacks. In addition to increasing crop productivity, this activity provided environmental benefits by reducing organic waste and economic benefits through lowering agricultural production costs.